SOME ASPECTS OF PROOF BY MEANS OF THE EXPERT STATEMENT - Tapalova R.B.; Nurmaganbet Y.T.; Izbassova A.B. (Хабаршы. Заң сериясы, 2019)
This article considers the problems arising at assessment of expert statements. The actual data important for the correct solution of criminal case is determined by testimonies of the suspect, victim, witness, witness having right for protection, the expert, the specialist; statement of the expert or specialist; mate-rial evidences; protocols of procedural actions and also statement of the expert or specialist. Assessment of proofs is considered in all scientific sources as the proof process element consisting in cogitative logical activities for determination of relevancy, admissibility and sufficiency of proofs for adoption of this or that proceeding decision. Further, authors emphasize that at assessment of the expert statement all important elements of activity of the expert have to be exposed to the analysis. The analysis of scientific validity of the expert statement – the most difficult moment in assessment of the expert statement. This analysis presents the known difficulty for the court because the expert statement – the result of the research conducted by the expert person on the basis of special knowledge. Knowledge of practical employees of law enforcement and judicial authorities in methodical bases of production of judicial expertize – one of conditions of objective assessment concerning compliance of the expert statement, the expert to circumstances of the considered case. Further, the article reveals basic provisions of the analysis of the expert statement in detail.